Complementary Molecular Data for Two Species from Herbarium Bogoriense: Sphaerobolus stellatus and Trichaleurina javanica - Yuliana, Meta; Maulana, Indra; Mulya, Sari; Fusvita, Laifa; Hermawan, Rudy (Jurnal Biologi UNAND, 2024)
A micro-mushroom namelyÂ Sphaerobolus stellatusÂ (BO 24422) and macro-mushroom namelyÂ Trichaleurina javanicaÂ (BO 24420) were found in Landscape Arboretum of IPB University. The latest identification used morphological characteristic and molecular study of Large Subunit DNA marker respectively. According to their identification, the database of fungal identification is commonly from Internal Transcribed Spacer (ITS) marker for molecular study. But both specimens,Â S. stellatusÂ BO 24422 andÂ T. javanicaÂ BO 24420, have not the ITS sequences yet. This research aim to study the molecular data of two specimens using ITS sequences. The method of this research used the molecular identification using internal transcribed spacer (ITS) primer: ITS 4 as a forward and ITS 5 as a reverse. Two phylogenetic trees were generated by Randomized Axelarated Maximum Likelihood (RAxML) Black box. Bootstrap (BS) values â‰¥ 90% were displayed on the phylogenetic treebranches. The result showed that the bootstrap value forÂ S. stellatusÂ BO 24422Â Â showed the good value as 96% classified asÂ S. stellatus. Then,Â T. javanicaÂ BO 24420Â Â had a better BS value with 93% classified asÂ T. javanica. The ITS is a general marker and very useful for molecular identification. Â